2004
DOI: 10.1093/intimm/dxh140
|View full text |Cite
|
Sign up to set email alerts
|

Specific subsets of murine dendritic cells acquire potent T cell regulatory functions following CTLA4-mediated induction of indoleamine 2,3 dioxygenase

Abstract: Murine dendritic cells (DCs) expressing indoleamine 2,3 dioxygenase (IDO) catabolize tryptophan and can suppress T cell responses elicited in vivo. Here, we identify specific subsets of splenic (CD11c+) dendritic cells competent to mediate IDO-dependent T cell suppression following CTLA4-mediated ligation of B7 molecules. IDO-competent DC subsets acquired potent and dominant T cell suppressive properties as a consequence of IDO up-regulation, as they blocked the ability of T cells to respond to other stimulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
223
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(233 citation statements)
references
References 43 publications
7
223
1
2
Order By: Relevance
“…3B). Systemic CpG-ODN administration induces IDO expression in the spleen It has been reported that activation of the enzyme IDO can inhibit T cell proliferation via depletion of tryptophan and/or via generation of suppressive tryptophan cleavage products [19,20]. We investigated whether the suppressive effect of systemic CpG-ODN application on T cell expansion is linked to IDO activity.…”
Section: Cpg-odn Treatment Impairs Antigen-specific Clonal T Cell Expmentioning
confidence: 99%
See 1 more Smart Citation
“…3B). Systemic CpG-ODN administration induces IDO expression in the spleen It has been reported that activation of the enzyme IDO can inhibit T cell proliferation via depletion of tryptophan and/or via generation of suppressive tryptophan cleavage products [19,20]. We investigated whether the suppressive effect of systemic CpG-ODN application on T cell expansion is linked to IDO activity.…”
Section: Cpg-odn Treatment Impairs Antigen-specific Clonal T Cell Expmentioning
confidence: 99%
“…T cell suppression by systemic CpG-ODN treatment is mediated by IDO activity For investigation of the functional relevance of IDO expression, the tryptophan analogue 1-methyl-tryptophan (1-MT), a well-established competitive inhibitor of IDO [19,20,22], was used. OVA-induced proliferation of CFSE-labeled OT-I cells was blocked by the presence of CpG-ODN in in vitro culture (Fig.…”
Section: Cpg-odn Treatment Impairs Antigen-specific Clonal T Cell Expmentioning
confidence: 99%
“…The modulated BMDC populations were clearly not refractory to LPS stimulation, but instead retained much of the normal LPSinduced transcription response. While some maturation of adoptively transferred tolerogenic DC is required to promote migration to the lymph nodes for Ag presentation to T cells [28], transcripts increased in response to LPS in this study encoded both classic proinflammatory agents, such as IL-1 and NOS2, and also well-characterized inhibitory molecules, such as IL-10, Indo and CD274 (PD-L1) [12,16,29] (Supporting Information Fig. 2A).…”
Section: Discussionmentioning
confidence: 93%
“…Numerous studies linking tolerance to DC maturation status have emphasized the importance of incomplete signaling to T cells [4][5][6][7][8], while others have highlighted dominant interactions delivering negative or co-inhibitory signals as critical [11][12][13][14]16]. More complete explanations advocate some balance of the two, with micro-environmental context of antigenic encounter, and the nature of the Ag itself proposed as key determinants in establishing this balance of signaling [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation